Identification and biochemical characterization of the novel mutation m.8839G>C in the mitochondrial ATP6 gene associated with NARP syndrome. (25th October 2013) - Blanco‐Grau, A.; Bonaventura‐Ibars, I.; Coll‐Cantí, J.; Melià, M. J.; Martinez, R.; Martínez‐Gallo, M.; Andreu, A. L.; Pinós, T.; García‐Arumí, E.
Abstract : Mutations in the ATP6 gene are reported to be associated with Leber hereditary optic neuropathy, bilateral striatal necrosis, coronary atherosclerosis risk and neuropathy, ataxia and retinitis pigmentosa (NARP)/maternally inherited Leigh syndromes. Here, we present a patient with NARP syndrome, in whom a previously undescribed mutation was detected in the ATP6 gene: m.8839G>C. Several observations support the concept that m.8839G>C is pathogenically involved in the clinical phenotype of this patient: (1) the mutation was heteroplasmic in muscle; (2) mutation load was higher in the symptomatic patient than in the asymptomatic carriers; (3) cybrids carrying this mutation presented lower cell proliferation, increased mitochondrial DNA (mtDNA) copy number, increased steady‐state OxPhos protein levels and decreased mitochondrial membrane potential with respect to isogenic wild‐type cybrids; (4) this change was not observed in 2959 human mtDNAs from different mitochondrial haplogroups; (5) the affected amino acid was conserved in all the ATP6 sequences analyzed; and (6) using in silico prediction, the mutation was classified as 'probably damaging'. However, measurement of ATP synthesis showed no differences between wild‐type and mutated cybrids. Thus, we suggest that m.8839G>C may lower the efficiency between proton translocation within F0 and F1 rotation, required for ATP synthesis. Further experiments are needed to fully characterize the molecular mechanisms involved in m.8839G>C pathogenicity . Abstract : We present a patient with NARP syndrome, in whom a previously undescribed mutation was detected in the ATP6 gene: m.8839G>C. Several observations support the concept that m.8839G>C is pathogenically involved in the clinical phenotype of this patient: (1) the mutation was heteroplasmic in muscle; (2) mutation load was higher in the symptomatic patient than in the asymptomatic carriers; (3) cybrids carrying this mutation presented lower cell proliferation, increased mtDNA copy number, increased steady‐state OxPhos protein levels and decreased mitochondrial membrane potential with respect to isogenic wild‐type cybrids; (4) this change was not observed in 2959 human mtDNAs from different mitochondrial haplogroups; (5) the affected amino acid was conserved in all the ATP6 sequences analyzed; and (6) using in silico prediction, the mutation was classified as 'probably damaging'.